DIGITAL MEDIA DONGENG BERBASIS ANIMASI SEBAGAI INOVASI PENDIDIKAN KARAKTER ANAK USIA DINI - Nuraina, Nuraina; Damayanti, Evi; Ikawati, Any (FKIP Universitas Wisnuwardhana, 2018)
The benefit of this research is the implementation of varied learning in national character education using digital media in storytelling. This research is an experimental study, whose purpose is to determine the effectiveness of fairytale digital-based learning models to shape the character of early childhood with measurable indicators on children's emotional intelligence and behavior. Stages of research include three stages, namely the preparation stage, data collection and data processing or data analysis. The preparation stage is done by determining the research object, the number of samples and indicators used. The indicators used to determine the success of the study include: a) the child begins learning by reading prayer; b) children share food/sharing with their friends; c) children lend stationery to their friends. The sample used is TK Akademika Students Malang. In the previous data collection phase the sample was divided into 2 groups, namely the experimental group and the control group that was subjected to treatment. Each group carried out a pre-test and post-test. Pre-test was given to test the similarity of the sample, while the post-test was used to determine the significance of a treatment. From the research results, it can be seen that there is an increase in the average value of the pre-test and post-test. The conclusion is that learning models with conventional methods such as fairy tales must be actualized in today's digital era. With this research, it can be seen that fairytale digital animation based learning can improve the superior character of students in the TK Akademika of Malang.Keywords: fairytale media, animation, character building, toodler